SUCCESSFUL MANAGEMENT OF HYDROAMNION IN A MURRAH BUFFALO - MEHRA, UMED SINGH; DUTT, RAVI; SEEMA (The Indian Journal of Animal Reproduction, 2023)
This communication reports a case of hydroamnion accompanying with fetal anomaly of maxilla and mandible and knuckling of both forelimbs in a full term Murrah buffalo. The defective fetus was delivered successfully with slight mutation without any post-partum complication to the dam.